Design, analysis and fabrication of malay traditional snacks cutter / Amirah Hanis Azman and Ahmad Najmie Rusli - Azman, Amirah Hanis; Rusli, Ahmad Najmie (School of Mechanical Engineering, 2022)
Malay Traditional Snacks Cutter is a new generation of the best solution any snack sellers can ever ask for. If you were walking at markets, be it a night market or a morning market, there will definitely be at least one hawker who sells Malay traditional snacks such as kuih talam, kuih lapis, kuih seri muka, and kuih kaswi. This innovation, created and fabricated with simple controls and operations, can simply reduce the cutting process duration, produce a more accurate size of each piece of snack, and make the cutting process tidier by just pushing a button. Most parts of the product are made out of aluminium sheet metals. Hence, welding, drilling, and milling will be involved during the fabrication process. Compared to the conventional methods, this innovation will be a big of help for snack sellers in order to reduce their time and to produce a better quality of snacks for their customers